2017
DOI: 10.21037/jtd.2017.01.09
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic yield and complications of open lung biopsies in kidney transplant patients with pulmonary disease

Abstract: Background: The purpose of this study was to assess the efficacy of open lung biopsy (OLB) in determining the specific diagnosis and the related complications in patients with undiagnosed diffuse pulmonary infiltrates.Methods: This single center, retrospective study included adult kidney transplant patients who underwent OLB. The patients had diffuse pulmonary infiltrates without definitive diagnoses and failed to respond to empiric antibiotic treatment. We analyzed the number of specific diagnoses, changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Complications were frequent (28.7% of OLBs) and associated with higher mortality rate. 105 A similar study comparing SOT and non-SOT patients with diffuse lung disease demonstrated a therapeutic management change frequency of 33%. 106 Percutaneous CT-guided lung biopsy has been evaluated in one series of SOT recipients with parenchymal lung nodule(s).…”
Section: • Laboratory Tests Not Obtained As Part Of the Initial Evalumentioning
confidence: 89%
See 1 more Smart Citation
“…Complications were frequent (28.7% of OLBs) and associated with higher mortality rate. 105 A similar study comparing SOT and non-SOT patients with diffuse lung disease demonstrated a therapeutic management change frequency of 33%. 106 Percutaneous CT-guided lung biopsy has been evaluated in one series of SOT recipients with parenchymal lung nodule(s).…”
Section: • Laboratory Tests Not Obtained As Part Of the Initial Evalumentioning
confidence: 89%
“…Open lung biopsy (OLB) was studied in a singlecenter kidney transplant population with bilateral lung infiltrates. 105 The overall OLB diagnostic yield was 85.1% with findings from 53% of OLBs resulting in a therapeutic management change. Complications were frequent (28.7% of OLBs) and associated with higher mortality rate.…”
Section: • Laboratory Tests Not Obtained As Part Of the Initial Evalumentioning
confidence: 96%
“…The mortality rate ranges from 10.6% to 66.6% in studies with renal transplant recipients requiring ICU care. 9,13,23,25,[29][30][31] This wide range can be explained by differences in ICU admission criteria and the high heterogeneity among patients, as the time frame from the transplant to ICU admission and the use of immunosuppressive agents are variable. Another potential explanation is the difference among the studies, some of them being single-center studies with a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the outcomes of the kidney transplant patients who need ICU care have varied significantly between studies, as the reasons for admission and the time length after transplant were different. [9][10][11][12][13] In addition, none of the ICU severity scoring systems has been tested in a general population of kidney transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…8,[16][17][18][19] Regarding the causes of ARF, the largest case series on the subject, a retrospective study involving 9 French centers specifically evaluating patients with ARF, showed bacterial pneumonia as the main cause (35.5%), followed by cardiogenic pulmonary edema (24, 5%). 8 In another smaller series from Turkey, also involving renal transplant patients with ARF, but at an earlier time after renal transplantation, the results were similar: bacterial pneumonia (56%) and cardiogenic pulmonary edema (44%).…”
Section: Discussionmentioning
confidence: 99%